2019
DOI: 10.1097/wnp.0000000000000559
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Utility of Ambulatory EEG Following Nondiagnostic Epilepsy Monitoring Unit Admissions

Abstract: Purpose: Epilepsy monitoring unit (EMU) admissions provide a definitive diagnosis for approximately three-quarters of patients. However, many patients do not receive a definitive diagnosis following EMU admission. Ambulatory EEG following nondiagnostic EMU admissions was evaluated as a means of providing a diagnosis for these patients. Methods: In this retrospective study, we performed a chart review of 62 pediatric and adult patients who had a 72-hour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
1
14
1
Order By: Relevance
“…Another study found that 32.3% of total sample reached a diagnosis within 24 hours, whereas the remaining patients who had events were equally distributed across the subsequent 24-hour intervals. 5 The diagnostic yield of such studies within the time collected remains undetermined. Kandler et al 17 found comparable diagnostic yield of ambulatory EEG-video (67%) to inpatient EEG-video monitoring (63%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study found that 32.3% of total sample reached a diagnosis within 24 hours, whereas the remaining patients who had events were equally distributed across the subsequent 24-hour intervals. 5 The diagnostic yield of such studies within the time collected remains undetermined. Kandler et al 17 found comparable diagnostic yield of ambulatory EEG-video (67%) to inpatient EEG-video monitoring (63%).…”
Section: Discussionmentioning
confidence: 99%
“…EEG-video recording is the mainstay of epilepsy centers; however, epilepsy monitoring units (EMU) frequently have long backlogs, waiting periods, and require patients to be in-hospital for several days. 1 To date, most literature on ambulatory EEG monitoring refers to EEG without video [2][3][4][5][6][7][8][9][10][11] and EEG-video has long been assumed to be an inpatient procedure. As of the past decade, technology has made ambulatory EEG-video possible.…”
Section: Introductionmentioning
confidence: 99%
“…Fox et. al 12 notes in a small sample of patients with previously nondiagnostic EMU stays (n = 62), half of the sample had sufficient diagnostic information by the end of 72 hours of ambulatory EEG, with 32.3% reaching a diagnosis within 24 hours, and the remaining equally distributed over the following two 24‐hour blocks. Primiani et.…”
Section: Introductionmentioning
confidence: 99%
“…Synergies of combining both and achieving a higher diagnostic yield have been demonstrated. 17 With the current electrode technology that is available, HVET recordings are limited to several days, often enough to obtain conclusive data to make a diagnosis. Repeat recordings may be required, but drug withdrawal in HVET, which is routine in the EMU, has not yet been attempted due to safety concerns.…”
Section: Current Challenges and Limitationsmentioning
confidence: 99%
“…The integration of hospital‐based services with non–hospital‐based services remains a fruitful ground for collaboration and innovation. Synergies of combining both and achieving a higher diagnostic yield have been demonstrated 17 …”
Section: Current Service Models For Hvetmentioning
confidence: 99%